2021
DOI: 10.3390/ma14237106
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Changing Glauber Salt Solution for Medical Applications in the 28–32 °C Interval

Abstract: (1) Background: The field of medicine requires simple cooling materials. However, there is little knowledge documented about phase change materials (PCM) covering the range of 28 to 40 degrees Celsius, as needed for medical use. Induced mild hypothermia, started within 6 h after birth, is an emerging therapy for reducing death and severe disabilities in asphyxiated infants. Currently, this hypothermia is accomplished with equipment that needs a power source and a liquid supply. Neonatal cooling is more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Pharmacological research has shown that Glauber's salt strongly stimulates the reticuloendothelial system, enhancing its phagocytic ability and anti-in ammatory effects [12,13]. By stimulating nerve re exes, it increases local blood ow, improves local blood circulation, restores vascular function, quickly reduces temperature and pain, and alleviates swelling [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological research has shown that Glauber's salt strongly stimulates the reticuloendothelial system, enhancing its phagocytic ability and anti-in ammatory effects [12,13]. By stimulating nerve re exes, it increases local blood ow, improves local blood circulation, restores vascular function, quickly reduces temperature and pain, and alleviates swelling [14].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, Glauber's salt has also been used for treating acute pancreatitis, gastrointestinal disturbances, carbuncles, furuncles, swelling and breast carbuncles [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1) Non-toxic to the human body, good biocompatibility, [93] ensuring the biocompatibility of PCM and its encapsulation materials is essential to avoid any adverse effects on the human body, thoroughly evaluate the toxicity and potential side effects of PCM-degradable products to ensure patient safety. 2) The phase change temperature should be in close proximity to the human body temperature (37 °C) or within the range of human body tolerance temperature (generally below 45-50 °C).…”
Section: The Advances Of Pcms In the Medical Fieldmentioning
confidence: 99%
“…Olson et al, (2021) reported the Glauber salt solution is a therapeutically appropriate PCM in the temperature interval required for cooling asphyxiated newborns. [74] PCMs utilized in biological applications often have high latent heat of fusion and low melting temperatures. From the standpoint of melting point and high latent heat of fusion, the FAs acetamide (AC), stearic acid (SA), palmitic acid (PA), myristic acid (MA), capric acid (CA), and lauric acid (LA), are prospective, plentiful, and economical materials for thermal usage.…”
Section: Eutecticmentioning
confidence: 99%
“…Olson et al., (2021) reported the Glauber salt solution is a therapeutically appropriate PCM in the temperature interval required for cooling asphyxiated newborns. [ 74 ]…”
Section: Applications Of Pcms In Life Sciencementioning
confidence: 99%